The association between neighborhood racial composition and menthol cigarette pricing in Boston, MA. (July 2019) - Kephart, Lindsay; Song, Glory; Henley, Patricia; Ursprung, W.W. Sanouri
Abstract: Objectives: To examine the relationship between neighborhood demographics and pack prices of four brands of mentholated and non-mentholated cigarettes in Boston, Massachusetts. Methods: Using tobacco pricing survey data collected July 2015 to June 2016, we examined cigarette prices in tobacco retailers (n = 689) located in block groups (n = 325) of Boston. Multilevel models examined both the association of menthol and non-menthol cigarette prices, and the percentage of retailers selling cigarettes below established minimum price in relation to neighborhood demographics. Results: Each 10 percentage point increase in the proportion of black residents per block group was associated with a price decrease of 3 cents for menthol cigarettes (p < 0.01). Each 10 percentage point increase in the proportion of black residents per block group was associated with a 19 percentage point increase in proportion of retailers selling menthol cigarettes ≥25 cents below minimum price (p < 0.01). Conclusion: Mentholated cigarettes were priced significantly lower in neighborhoods of color in Boston. Strengthened pricing laws, with consideration given to menthol products in the retail environment, may be needed to address environmental contributors to smoking disparities. Highlights: People of color in Boston are impacted by menthol cigarettes in different ways than white residents. The price of Newport menthol cigarettes decreases in neighborhoods with greater proportions of black residents. More retailers sell Newport cigarettes signficantly below minimum price in neighborhoods with more black residents. Lower prices, in conjunction with advertisements and social norms, may contribute to inequities in menthol smoking rates.